2006
DOI: 10.1093/geronb/61.6.s290
|View full text |Cite
|
Sign up to set email alerts
|

Social Status, Risky Health Behaviors, and Diabetes in Middle-Aged and Older Adults

Abstract: Risky health behaviors are key predictors of incident diabetes in both age groups. Economic resources also play an important protective role in incident diabetes in midlife but not in older age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 45 publications
2
34
0
2
Order By: Relevance
“…In our study we observed that socioeconomic health was inversely related to the prevalence of diabetes, both for each country analysed individually and for the overall data. In accordance with other studies we have found that diabetes morbidity is associated with having a disadvantaged SEP [2,3,[8][9][10][11][12]. Previous studies that have analysed inequalities in diabetes mortality also have shown that people with a lower SEP have a higher risk of dying from diabetes [13][14][15].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study we observed that socioeconomic health was inversely related to the prevalence of diabetes, both for each country analysed individually and for the overall data. In accordance with other studies we have found that diabetes morbidity is associated with having a disadvantaged SEP [2,3,[8][9][10][11][12]. Previous studies that have analysed inequalities in diabetes mortality also have shown that people with a lower SEP have a higher risk of dying from diabetes [13][14][15].…”
Section: Discussionsupporting
confidence: 91%
“…This association was shown in both diabetes morbidity studies [3,8,[10][11][12] and in diabetes mortality studies [13][14][15]. Recent studies have reported that this association is explained in part by health behaviours and obesity [8,[16][17][18].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, adult onset diabetes mellitus is far more prevalent in blacks than whites (Brancati et al, 1996;Wray et al, 2006) and the excess prevalence among blacks is greater among women than men (Robbins et al, 2000). Diabetes is associated with physical disability.…”
Section: Disparities In Chronic Diseases Impairments and Disabilitymentioning
confidence: 99%
“…Nustatyta, jog daugeliu atveju cukrinio diabeto susirgimo priežastys yra biologinės, tačiau Lietuvos ir užsienio straipsniuose pateikiama įrodymų, kad liga gali atsirasti ir dėl įvairių psichologinių bei socialinių veiksnių (Knol et al, 2006;Ostrauskas, Radzevičienė, 2006;Wray, Alwin, McCammon, Manning, Best, 2006). Svarbu paminėti, jog ši sunki lėtinė liga sukelia ne tik zinių komplikacijų ar pokyčių, bet ir psichologinių bei socialinių pasekmių, pavyzdžiui, depresiją (Friedmann et al, 2009), dažną pykčio pasireiški-mą (Yi, Vitaliano, Weinger, 2008), sumažėjusią savivertę (Dementjeva, Pileckaitė-Markovienė, Cap, 2006), padidėjusią socialinės izoliacijos riziką (Sacco, Yanover, 2006), padažnėjusius kon iktus tarp šeimos narių ar/ir partnerio (-ės) (Gruszczynska, 2006), padidėjusią sergančiojo priklausomybę nuo šeimos narių (Trief, 2003), sumažėjusį produktyvumą darbe (Lavigne, Phelps, Mushlin, Lednar, 2003).…”
Section: įVadasunclassified